Analisis Manajemen Risiko Perbankan Pada Bank Umum Di Indonesia Periode 2019-2023 - Putra, Moh. Rizqy Eka; Pasaribu, Gymnastiar Eka Aurillina; Fisabilillah, Ladi Wajuba Perdini; Aji, Tony Seno (Jurnal Ekonomika : INDEPENDEN, 2025)
This research analyzes the impact of NPL (Non-Performing Loans), LDR (Loans to Deposits Ratio), and BOPO (Operating Expenses to Operating Income) on ROA (Return on Assets) in commercial banks in Indonesia during 2019-2023. Using secondary data from financial reports of banks registered on the IDX, multiple regression analysis was carried out using Eviews 12. Purposive sampling technique was used to select six banks that met the criteria, so that the total sample consisted of 30 banks. The research results show that NPLs have a significant negative impact on ROA, reducing bank profitability. LDR and BOPO do not significantly affect ROA, indicating that credit effectiveness and operational efficiency do not directly affect profitability. CAR is also not significant to ROA, possibly due to the absence of profitable capital utilization. Overall, credit risk management and asset quality influence profitability more than operational efficiency and use of funds